The Effect of Thyroxine Hormone (T4)On Feed On The Growth and Survival Rate of Baung (Hemibagrus nemurus) - Pasaribu, Jeriko; Rusliadi, Rusliadi; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            This research was conducted in December 2019 - January 2020 located in the Laboratory of Cultivation Technology. The purpose of this study is to find out the best dose of thyroxine hormone on feed to increase the growth and survival of baung. This study uses a completely randomized design (CRD) consisting of 4 treatments and 3 replays. The treatment in this study was the addition of thyroxine hormone in feed i.e. P0 control (Without hormone), P1(3 mg/kg feed), P2(6 mg/kg feed), P3(9 mg/kg feed). The results showed that thyroxine hormone 9 mg/feed was the best result resulting in absolute weight growth 6.17g, absolute long growth 3.17cm, specific growth rate of 2.65%, feed efficiency of 75.84%, and survival rate 95.55%. Water quality parameters during the study were temperature 26-27.3 oC, pH 6-7, DO 4.12-5.57 ppm and ammonia 0.03-0.09 mg/L.Keywords :Thyroxine Hormone, Baung Fish (Hemibagrus nemurus), Feed.